2000
DOI: 10.7164/antibiotics.53.1168
|View full text |Cite
|
Sign up to set email alerts
|

Double Stage Activity in Aminoglycoside Antibiotics.

Abstract: Fourteen different aminoglycoside antibiotics (AGs) were challenged with aminoglycoside acetyltransferases (AACs) of actinomycete origin in order to examine their 'double stage activity' that is arbitrarily defined as antibiotic activity retainable after enzymatic modification. In kanamycin (KM)-group AGs tested [KM, dibekacin (DKB), amikacin and arbekacin (ABK)], ABKretained activity after acetylations by AAC(3), AAC(2') and AAC(6'). DKBalso retained a weak activity after acetylation by AAC(2'). In gentamicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
1
17
0
2
Order By: Relevance
“…As anticipated, the high catalytic efficiency of the enzyme against most 4,6-disubstituted aminoglycosides translates into a 64 -128-fold increase in the MICs of these antibiotics over background levels (Table 1) Ϫ1 s Ϫ1 , respectively, the enzyme does not confer resistance to these antibiotics. Previous studies have demonstrated that arbekacin acetylated at the 3-, 2Ј-, or 6Ј-positions retains antibiotic activity against Gram-positive and Gram-negative bacteria, despite modification (27,28). Our data suggest that the product of arbekacin phosphorylation may also retain antibacterial activity.…”
supporting
confidence: 49%
“…As anticipated, the high catalytic efficiency of the enzyme against most 4,6-disubstituted aminoglycosides translates into a 64 -128-fold increase in the MICs of these antibiotics over background levels (Table 1) Ϫ1 s Ϫ1 , respectively, the enzyme does not confer resistance to these antibiotics. Previous studies have demonstrated that arbekacin acetylated at the 3-, 2Ј-, or 6Ј-positions retains antibiotic activity against Gram-positive and Gram-negative bacteria, despite modification (27,28). Our data suggest that the product of arbekacin phosphorylation may also retain antibacterial activity.…”
supporting
confidence: 49%
“…Resistance levels were determined by the agar dilution method using Mueller Hinton II medium (Becton Dickinson, Franklin Lakes, NJ) containing AG at concentrations of 0 to 100 m g/ml as described previously [6].…”
Section: Determination Of Ag Antibiotic Resistancementioning
confidence: 99%
“…The enzymes differ in their substrate specificity and are named according to the site that they modify on the antibiotic molecule. In MRSA, five AME-encoding genes, aph(3Ј), aad(4Ј,4Љ), aad (6), aph (9), and aac(6Ј)/aph(2Љ), have been reported [3]. In particular, the bifunctional enzyme, AAC(6Ј)/APH(2Љ), is of therapeutic importance because it is able to modify arbekacin (ABK), which is an anti-MRSA drug used in Japan [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ABK retained antimicrobial activity after enzymatic acetylation by AAC(3), AAC(2 0 ) and AAC(6 0 ). 15 Kondo et al 6 reported that when ABK was inactivated by crude enzyme prepared from an ABK-resistant MRSA having AAC(6 0 )/APH(2 00 ), phosphorylated ABK was obtained as a major inactivated product. Therefore, phosphorylation may be much critical than acetylation for the inactivatiton of ABK.…”
mentioning
confidence: 99%